2020
DOI: 10.7150/jca.46805
|View full text |Cite
|
Sign up to set email alerts
|

Early response and pathological complete remission in Breast Cancer with different molecular subtypes: a retrospective single center analysis

Abstract: Purpose: To evaluate the association of clinical early response and pathological complete remission (pCR) in breast cancer patients with different molecular subtypes. Materials and methods: Breast cancer patients who received neoadjuvant treatment (NAT) with clinical early response assessment from October 2008 to October 2018 were retrospectively analyzed. Clinical early response was defined as tumor size decreasing ≥30% evaluated by ultrasound after two cycles of NAT. Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…The overall pCR rate of 41% observed in this study and the difference in pCR achievement between early responders and non-responders is concordant with published studies [ 26 , 29 , 57 ]. In this study, a positive influence of platinum salts on pCR was observed in all analyzed subgroups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The overall pCR rate of 41% observed in this study and the difference in pCR achievement between early responders and non-responders is concordant with published studies [ 26 , 29 , 57 ]. In this study, a positive influence of platinum salts on pCR was observed in all analyzed subgroups.…”
Section: Discussionsupporting
confidence: 93%
“…The predictive role of these markers was evaluated more often with regard to pCR achievement than ECR [ 53 , 54 ]. Hong et al retrospectively evaluated different characteristics of responders and non-responders [ 26 ]. Unlike the presented study, patients with different molecular subtypes were included, differences in cT were not found, and the proliferative index was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 25 included studies involved 8767 patients, and the publication years of articles were from 2015 to 2020. Among them, 18 studies were retrospective cohort studies [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and 7 studies were prospective cohort studies [32][33][34][35][36][37][38]. Various types of NAT were utilized in the included studies, including anthracycline-based drugs, taxanes, and platinum plus docetaxel.…”
Section: Literaturementioning
confidence: 99%
“…PFS and OS were evaluated using the Kaplan–Meier curve and were compared using log‐rank test. All statistical analyses were performed using SPSS version 25.0 17 …”
Section: Methodsmentioning
confidence: 99%